Tourism Development in Gjoa Haven, Nunavut and Around the Wrecks of the HMS Erebus and HMS Terror National Historic Site ... - Weber, Melissa; Dawson, Jackie; Carter, Natalie Ann (My University, 2021)
Tourism is a growing industry within Inuit Nunangat and an important part of Nunavut’s economy. The discovery of the Franklin Wrecks, on September 2, 2014 and September 3, 2016, is expected to generate tourism demand and related tourism development opportunities. However, what is unclear is 1) what the potential visitor experience could look like; and 2) the feasibility of developing a visitor experience. The purpose of this research project was to document community knowledge and perspectives on tourism development to assist in tourism planning, management and development at the Franklin Wrecks sites. This report reflects the knowledge and opinions gathered through interviews with community members in Gjoa Haven who were identified as key knowledge holders and/or experts. The specific project objectives were to... 1. Identify community perspectives and recommendations for tourism development; 2. Document community perspectives on the Wrecks of the HMS Erebus and HMS Terror National Historic Site as a ...